2018
DOI: 10.1111/cid.12655
|View full text |Cite
|
Sign up to set email alerts
|

Implant rehabilitation of the edentulous jaws: Does tilting of posterior implants at an angle greater than 45° affect bone resorption and implant success?: A retrospective study

Abstract: Posterior implants tilted >45° to eliminate distal cantilever may be as safe as those tilted less in severely atrophic jaws rehabilitated with immediately loaded, full-arch prostheses supported on 4 implants. Further prospective studies on larger samples of patients and implants and with longer follow-up are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…In this study, the model of FPD supported by two tilted dental implants provides a new design with a reduced risk of bone loss and implants failure by reducing stress concentrations rate. Moreover, The FE results are qualitatively in agreement with those obtained by previous studies 4,8,13,17,22,23,[35][36][37][38][39][40] although the geometrical models and loading condition that were used are different from those used in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the model of FPD supported by two tilted dental implants provides a new design with a reduced risk of bone loss and implants failure by reducing stress concentrations rate. Moreover, The FE results are qualitatively in agreement with those obtained by previous studies 4,8,13,17,22,23,[35][36][37][38][39][40] although the geometrical models and loading condition that were used are different from those used in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Also, no evidence suggested that tilted implants are associated with a higher incidence of biomechanics complications. 35 Moreover, Malchiodi et al, 36 in a retrospective study on 142 implants inserted in the maxilla and mandible, using an All-on-Four approach, with immediate loading noticed that implant tilting angle was not correlate with marginal bone loss and concluded that implants tilted . 45°to eliminate distal cantilever were as safe as those tilted less in severely atrophic jaws rehabilitated with immediately loaded, full-arch prostheses supported on four implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to avoid bone augmentation include adjusting the implant diameter to the volume of the remaining bone by using narrow or short implants, 7,8 receiving anchorage from the zygomatic bone by usage of zygoma implants, 9 or modifying the implant placement in the available maxillary bone by angulating the implants to achieve maximal bone anchorage. 10,11 Additional advantage of avoiding bone augmentation is that patients can be potentially provided prosthesis within 24 hours of implant placement. This concept known as immediate implant loading (defined as prosthesis loaded onto the dental implant within 1 week of implant placement) is being increasingly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Hence clinical implant treatment procedures that avoid bone augmentation are being increasingly sought after. Strategies to avoid bone augmentation include adjusting the implant diameter to the volume of the remaining bone by using narrow or short implants, receiving anchorage from the zygomatic bone by usage of zygoma implants, or modifying the implant placement in the available maxillary bone by angulating the implants to achieve maximal bone anchorage …”
Section: Introductionmentioning
confidence: 99%